Interplay between evanescence and disorder in deep subwavelength photonic structures - Hanan Herzig Sheinfux (Nature Portfolio, 2016)
Features much smaller than the wavelength are not expected to have a significant impact on the transport of a wave. Here, the authors show that Anderson localization can dominate light transport in a one-dimensional disordered system, even when the disordered features are a thousand times smaller than the wavelength.